More management is needed to improve the effectiveness of artificial grassland in vegetation and soil restoration on the three-river headwaters region of China - Wang, Nengyu; Wan, Jiayi; Ding, Mingjun; Zhang, Hua; Li, Shicheng; Liu, Linshan; Zhang, Yili (Frontiers in Plant Science, 2023)
Establishing an artificial grassland is a common measure employed to restore heavily degraded alpine grasslands for regional sustainability. The Three-River Headwaters Region (TRHR) in China has significant areas of black-soil-type grassland which is typified by heavy degradation; nearly 35% of the grassland regions of the TRHR has degraded into this type. There are different plant community types of black-soil-type grasslands, however, it is not clear which restoration measures should be adopted for different kinds of black-soil-type grasslands. Here, we investigate the plant community characteristics and soil physicochemical properties of artificial grasslands, two types of black-soil-type grasslands, and native undegraded grassland in the TRHR, then analyzed the direct and indirect interactions between the plant and soil properties by partial least squares path models (PLS-PM). Our results revealed that establishing artificial grassland significantly increased aboveground biomass and plant community coverage, and also decreased plant species richness and diversity and soil water content, soil organic carbon and total nitrogen in the 0-10 cm soil layer as compared with black-soil-type grasslands. Plant community diversity had a positive effect on plant community productivity, soil nutrient, and soil water content in native undegraded grassland. These results suggest that more management interventions are needed after establishing an artificial grassland, such as reducing dominant species, water regulation in the A.frigida-dominated meadow, diversifying plant species (i.e., Gramineae and sedges), and fertilizer addition.